Pengaruh Rasio Lemak Padat Dan Refined Bleached Deodorized Palm Oil (RBDPO) Pada Pembuatan Shortening - Hariani, Razita; Nur Asma Deli (Politeknik Kampar, 2023)
Refined Bleached Deodorized Palm Oil (RBDPO) is an oil produced from fresh fruit of the oil palm (Elais guineensis Jacq.) by going through an oil refinery process. RBDPO consists mostly of C16 palmitate fat of 44% which can be applied to shortening products. Shortening is a product derived from RBDPO oil, shortening is a processed product of semi-solid oil emulsions. This study aims to determine the process of making shortening, to find out the results of the analysis of shortening quality, to find out the optimum ratio for making shortening. The ratio of solid fat:RBDPO used in the manufacture of this shortening is 100:0, 80:20, 60:40, 40:60, 20:80, 0:100. Optimum results in the manufacture of shortening based on physical and chemical analysis, obtained with a ratio of 80% solid fat: 20% RBDPO with a moisture content of 0.29%, free fatty acid content of 0.54% and a peroxide value of 0.115 mek O2/kg.